Pengaruh Beban Kerja terhadap Kinerja Karyawan Perumda Air Minum Tirta Ratu Samban Bengkulu Utara Dimediasi Perilaku Cyberloafing - Praningrum; Maulida Nabila Ovika (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
By using cyberloafing behavior as a mediating variable, this research aims to find out how workload impacts employee performance at Perumda Air Minum Tirta Ratu Samban, North Bengkulu. The author of this research used quantitative methods. Data was collected by distributing questionnaires to employees using Google Form. Although the questionnaire was distributed to one hundred workers, only 65 were usable. The influence of the independent variable on the dependent variable was evaluated using the multiple linear regression method during data collection. This research uses a non-probability sample. The results of the research explain that this research has the conclusion that there is a significant relationship between the workload variable and the cyberloafing variable, the workload variable with the performance variable, and the cyberloafing variable with performance, as well as the workload variable with cyberloafing through the performance variable.